Reduced CeO2 (111) ordered phases as bulk terminations: Introducing the structure of Ce3O5 - Murgida, Gustavo Ezequiel (2018)
Reduced ceria (CeO2−x ) has a rich phase diagram comprising a variety of bulk phases with stoichiometries ranging from CeO2 to Ce2O3 as the reduction conditions are increased. Some observed reduced ceria (111) surface reconstructions are terminations of stable bulk phases, such as √7 × √7, whereas others are not associated with any known stable phases, namely, √7 × 3, 3 × 3, and √3 × √3. In this paper, we analyze different periodic reconstructions of reduced ceria (111) surfaces within a theoretical framework. We describe the surfaces of stable bulk phases and elucidate the structure of the observed periodicities not corresponding to terminations of known stable bulk phases. Extending the 3 × 3 and √3 × √3 terminations into a bulk structure, we find a new quasistable Ce3O5 bulk phase, which explains both periodicities. On the contrary, the √7 × 3 surface structure cannot be extended into a bulk but stabilizes as a very thin overlayer. We also analyze other reported bulk structures with stoichiometry close to the Ce3O5 one, namely, the C-type Ce2O3+δ bulk phase, which cannot describe the observed terminations. Our goal is to provide a unified picture to describe the road map of CeO2−δ (111) surface reconstructions and, when possible, their relationship to reduced ceria bulk phases.